Comparative study of PAH removal efficiency under absence of molecular oxygen: effect of electron acceptor and hydrodynamic conditions (2007)
A series of experiments were made in order to compare the removal efficiency of a mixture of four PAHs (naphthalene, phenanthrene, pyrene, and benzo[a]pyrene), under different electron acceptor (NO3 −, SO4 −2) and hydrodynamic conditions (stagnation and high shear). In all cases naphthalene showed the highest removal efficiency (from 69% up to 100%) as compared with the other PAHs. The fastest rate was obtained for the denitrifying-high shear condition followed by denitrification-no shear, sulfate-reduction-high shear and the lowest for sulfate reduction-no shear. However, most of the perceived removal of the heavier PAHs could be due to aging. No lag time was observed for the denitrifying experiments, and the denitrification rate was the same regardless of the hydrodynamic condition. A lag time of 64 d was observed under conditions of sulfate reduction and high shear. Sulfate reduction did not commence under no shear conditions. No toxic effect was observed for the four PAH mixture under all the conditions tested.